Vector-Matrix Method of Numerical Implementation of the Polynomial Integral Volterra Operators - Ivanyuk, V.A.; Fedorchuk, V.A. (Математичне та комп'ютерне моделювання. Серія: Технічні науки, 2020)
The article deals with the quadrature method for the numerical implementation of polynomial integral operators. With the computer implementation of Volterra-type integral models, the typical problem is the accumulation of calculations at each step of the computational process. For its acceleration it is suggested to apply the vector-matrix approach. The suggested approach is based on quadrature methods: rectangles, trapezoids, and Simpson's. For homogeneous polynomial integral Volterra operators of the first-, second- and third-degree, respectively, the objects in the form of vectors, matrices, and three-dimensional structures containing the coefficients of the corresponding quadrature formulas have been constructed. У статті розглядається метод квадратур для числової реалізації поліноміальних інтегральних операторів. При комп’ютерній реалізації інтегральних моделей типу Вольтерри характерною проблемою є накопичення кількості обчислень на кожному кроці обчислювального процесу. Для його пришвидшення пропонується застосовувати векторно-матричний підхід. В основі запропонованого підходу лежать методи квадратур: прямокутників, трапецій, Сімпсона. Для однорідних поліноміальних інтегральних операторів Вольтерри першого, другого та третього степеня побудовано, відповідно, у вигляді векторів, матриць та тривимірних структур об’єкти, які містять коефіцієнти відповідних квадратурних формул.